Benefits of 5S Implementation and recommendation in the Defense Industry: A Literature Review - Hafidz, Aulia; Soediantono, Dwi (IJOSMAS, 2022)
The purpose of this article is to explore the benefits of implementing 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) in various industries and provide recommendations to be applied to the defense industry. The method of writing this article is a literature review, which is a review by collecting, understanding, analyzing and then concluding as many as 25 international journal articles published from 2015 to 2021 regarding the application of the 5S method in various industrial sectors and the defense industry. The analysis used used 25 content analysis of journal articles. The data that has been collected is then looked for similarities and differences and then discussed to draw conclusions. The results of the literature review analysis state that the application of 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) can improve occupational safety and health, quality, productivity, delivery, cost, morale in various industries so that the 5S method (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) is recommended to be applied in the defense industry.